Characteristics of Bacillus stearothermophilus mutants blocked in catabolic function. - Rowe, J J (1976)
With polyacrylamide disc gel electrophoresis and specific staining, it was demonstrated that one mutation involving the alcohol dehydrogenase of a double mutant of Bacillus stearothermophilus 1503 apparently prevented enzyme synthesis, and another lesion in the same organism resulted in synthesis of an inactive form of aconitase. Some properties of the double mutant and two fumarase mutants are discussed in relation to similar mutants derived from Bacillus subtilis.